Implementation of the Deep Learning Approach in Islamic Education Learning in Elementary School - Purwoko, Purwoko; Adibah, Ida Zahara; Nasikin, Moch; Mahmud, As’ad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study investigates the implementation of a deep learning approach in Islamic education at SDIT Nurul Islam Tengaran. Deep learning prioritizes meaningful understanding, critical thinking, and active learner engagement. Employing a qualitative case study design, data were gathered through classroom observations, in-depth interviews with teachers and students, and an examination of instructional documents. Data analysis followed an interactive model with triangulation across sources, methods, and perspectives to ensure validity and strengthen the credibility of findings. The results indicate that the application of deep learning in Islamic education remains at an early developmental stage and has not been fully optimized. The instructional design integrates Qur’anic studies, religious practices, and extracurricular activities as interconnected pathways for linking conceptual knowledge with students’ real-life experiences. Several supporting factors were identified, including a school culture grounded in Islamic values, teachers’ intrinsic motivation, and alignment with curriculum policy. However, notable challenges persist, such as limited teacher competence in designing deep learning–oriented strategies, insufficient contextual learning materials, and restrictions related to time and institutional resources. This study recommends enhancing teacher professional development, developing reflection-based teaching modules, and promoting collaborative planning between Islamic education teachers and other subject educators to foster holistic and transformative learning. The findings are expected to contribute to the development of adaptive, innovative, and contextually responsive Islamic education practices that meet the learning demands of 21st-century students.